The Ukrainian Intelligentsia and Genocide : The Struggle for History, Language, and Culture in the 1920s and 1930s - Malko, Victoria A. (Academic Studies Press, 2024)
This study focuses on the first group targeted in the genocide known as the Holodomor: the Ukrainian intelligentsia, or the “brain of the nation,” to use the words of Raphael Lemkin, who coined the term genocide and enshrined it in international law. The study’s author examines complex and devastating effects of the Holodomor on Ukrainian society during the 1920–1930s. Members of the intelligentsia had individual and professional responsibilities. They resisted, but they were eventually forced to serve the Soviet regime. The Ukrainian intelligentsia was virtually wiped out, including most of its writers and a third of its teachers, and the remaining cadres faced a choice without a choice if they wanted to survive. The author analyzes how and why this process occurred and what role intellectuals, especially teachers, played in shaping, contesting, and inculcating history. Crucially, the author challenges Western perceptions of the all-Union famine that was allegedly caused by ad hoc collectivization policies, highlighting the intentional nature of the famine as a tool of genocide, persecution, and prosecution of the nationally conscious Ukrainian intelligentsia, clergy, and grain growers. The author demonstrates the continuity between Stalinist and neo-Stalinist attempts to prevent the crystallization of the nation and subvert Ukraine from within by non-lethal and lethal means